Stakeholder Feedback System for Curriculum Design and Improvement – A Case Study - Misra, Rachita; Priyadarshini, Rojalina (Journal of Engineering Education Transformations, 2018)
With the increase in the number of universities and autonomous institutes there is a need of developing suitable curriculum and its updates to maintain the quality of education and increase employability. This is very challenging especially for engineering education in Information technology and Computer Engineering, as the technology changes too fast and the nature of job market keep changing accordingly. This poses a practical problem to keep-up a matching pace of change in academics. To keep the quality of education at par with reputed institutes at national and international level the regulators like All India Council of Technical Education (AICTE) and National Board of Accreditation (NBA) of Indian Government provide norms and guidelines on implementing curriculum following Outcome Based Education (OBE). This paper examines the stakeholder's expectations for the type course modules included during the 4-year study of the B.Tech program, affecting the teaching learning approach and the outcome. The use of a feedback system from stakeholders has been presented which can be used for the design and improvement of course curriculum. The idea and concepts have been explained by taking the B.Tech IT program's curriculum development as a case study for implementing the new autonomous syllabus as an improved version of the existing university curriculum.